In vitro screening of Andrographis paniculata (Hempedu bumi) for antibacterial activity using disc diffusion method - Sule, Abubakar; Abd. Samah, Othman; Omar, Muhammad Nor; Ahmed, Qamar Uddin (2009)
The increasing prevalence in multidrug resistant strains of bacteria and the recent appearance of strains with reduced susceptibility to antibiotics raises the specter of untreatable bacterial infections and adds urgency to the search for new infection-fighting strategies1. The plant Andrographis paniculata (Hempedu Bumi) is used in traditional medicinal practice for the treatment of various chronic and infectious diseases some of bacterial origin2.. This study was carried out to evaluate the antibacterial activity of organic extracts of A. paniculata leaves and stems against 8 pathogenic bacterial strains: Staphylococcus aureus, Streptococcus pyogenes, Bacillus anthrax Micrococcus luteus, Klebsiella pneumoniae, Proteus vulgaris, Pseudomonas aeroginosa and Proteus mirabilis using disc diffusion method. Dried ground powdered leaves and stems were extracted with petroleum ether, dichloromethane, ethyl acetate, acetone, ethanol and finally with methanol using the soxhlet extraction. The result obtained vividly revealed that the different extracts differed significantly in their antibacterial properties with Dichloromethane extract being the most effective followed by acetone, ethyl acetate, methanol, petroleum ether and lastly ethanol extract. In general, the leaves exhibited strong antibacterial activity than the stems extracts; but all the extracts exerted very good broad spectrum activity against all tested microorganisms. The results explicitly suggest that there might be polar compounds present in the leaves and stems of A. paniculata as the main active ingredients. This finding forms a strong basis for further studies on screening of A. paniculata extracts for the exploration of potent antibacterial agents.